Preprocedural fasting for contrast-enhanced CT: when experience meets evidence - Heng Liu (SpringerOpen, 2021)
Abstract Traditional preparatory fasting policy prior to iodinated contrast media (ICM) assisted contrast-enhanced CT (CECT) examinations lacks methodologically acceptable evidence. Considering the possible negative effects of preprocedural fasting, the latest European Society of Urogenital Radiology guidelines V10.0 and American Committee of Radiology 2021 guidelines clearly state that preprocedural fasting is not recommended prior to routine intravenous ICM administration. This comprehensive and detailed Review presents the current global dietary preparation policies, potential harm of excessive fasting, and a systematical and well-bedded description of practice advancements of dietary preparation. The evidences revealed that there has been no single instance of vomiting-associated aspiration pneumonia due to the undemanding implementation of preparatory fasting prior to CECT yet. Non-fasting would not increase the incidence of emetic symptoms and the risk of aspiration pneumonia. Not every patient should undergo all CECT examinations without preparatory fasting. There is still much more refinement to be done on the preparatory fasting policy. Changes in traditional preparatory fasting policy will make positive and significant implications on clinical practice. This Review aims to provide operational guidance and suggestions for practitioners and policymakers, motivate efficient, reasonable, safe and normative ICM usage, and achieve optimal patient clinical benefits and high-quality radiological care practices.